Exposure of LS-180 Cells to Drugs of Diverse Physicochemical and Therapeutic Properties Up-regulates P-glycoprotein Expression and Activity - Alaa H Abuznait; Shawn G Patrick; Amal Kaddoumi (Frontiers Media S.A., 2011)
Purpose. Drug transporters are increasingly recognized as important determinants of variability in drug disposition and therapeutic response, both in pre-clinical and clinical stages of drug development process. The role P-glycoprotein (P-gp) plays in drug interactions via its inhibition is well established. However, much less knowledge is available about drugs effect on P-gp up-regulation. The objective of this work was to in vitro investigate and rank commonly used drugs according to their potencies to up-regulate P-gp activity utilizing the same experimental conditions. Methods. The in vitro potencies of several drugs of diverse physicochemical and therapeutic properties including rifampicin, dexamethasone, caffeine, verapamil, pentylenetetrazole, hyperforin, and β-estradiol over broad concentration range to up-regulate P-gp expression and activity were examined. For dose-response studies, LS-180 cells were treated with different concentrations of the selected drugs followed by P-gp protein and gene expressions analyses. P-gp functionality was determined by uptake studies with rhodamine 123 as a P-gp substrate, followed by Emax/EC50 evaluation. Results. The results demonstrated a dose-dependent increase in P-gp expression and activity following treatments. At 50 uM concentration (hyperforin, 0.1 uM), examined drugs increased P-gp protein and gene expressions by up to 5.5 and 6.2-fold, respectively, while enhanced P-gp activity by 1.8-4-fold. The rank order of these drugs potencies to up-regulate P-gp activity was as following: hyperforin >>> dexamethasone ~ beta-estradiol > caffeine > rifampicin ~ pentylenetetrazole > verapamil. Conclusions. These drugs have the potential to be involved in drug interactions when administered with other drugs that are P-gp substrates. Further studies are needed to in vivo evaluate these drugs and verify the consequences of such induction on P-gp activity for in vitro-in vivo correlation purposes. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.